Uniaxial fatigue study of a natural-based bio-composite material reinforced with fique natural fibers (Fracture and Structural Integrity, 2024)
This research addresses environmental concerns by exploring environmentally friendly composite materials as substitutes for non-biodegradable synthetic fibers. The study proposes the development of polymer matrix composites reinforced with natural fique fibers, sourced from a plant cultivated in Colombia. A BioPoxy 36 polymer matrix with a high carbon content was used and reinforced with fique fabric using the vacuum-assisted lamination method. To improve the adhesion between the fibers and the matrix, an alkaline chemical treatment was applied to the fiber using 2% sodium hydroxide by weight. Mechanical properties were assessed through ASTM D3039 tensile and ASTM D3479 fatigue tests. A fractographic analysis was also conducted to identify the different modes of failure present. In terms of material degradation, distinct stages were observed, characterized by stiffness loss and loss factor indicators. The Coffin-Manson model was used to obtain the strain life curve for R = 0.1, using these factors as criteria. The static properties of the composite reinforced with fique fibers indicate an increase of 45% in ultimate strength, 145% in strain, and 27% in Young's modulus compared to the unreinforced matrix. In terms of dynamic properties, the elastic modulus showed a maximum variation of up to 7.88%. Electron microscopy reveals the failure mechanism, a distinct separation between the matrix and the fiber can be observed as a result of mechanical stress. The analysis reveals the brittle fracture of the hard fique fiber and some matrix separation, as well as possible fractured bubbles that may have occurred during the manufacturing process.
Keywords: Uniaxial fatigue; Bio-composite; Natural fibers; Fique; Fiber reinforced material.